The Effect of E-Service Quality and Perceived Value on Telkomsel's E-Customer Loyalty on Mytelkomsel App Users - Cahyo Adi Prasetyo; Nina Nurani (Budapest International Research and Critics University, 2022)
This study aims to be able to explain how much influence e-service quality and perceived value have on Telkomsel's e-customer loyalty to MyTelkomsel App users in Bandung City. The research method used is descriptive using quantitative methods involving 400 respondents who use the MyTelkomsel App in Bandung City. The sampling technique used is non-probability sampling with a purposive sampling type. In this study, respondent data was processed using the SPSS 25 for Windows application. The results of the study based on descriptive analysis for the e-service quality variable are already in the excellent category by 89%, as well as for the perceived value variable is already in the excellent category by 90%, and the e-customer loyalty variable is already in the excellent category by 87%. E-customer quality and perceived value have a positive and significant effect on e-customer loyalty with a magnitude of influence of 51.5% and the remaining 48.5% influenced by other factors that were not studied.